Comparison of reproductive parameters for populations of eastern North Pacific common dolphins: Delphinus capensis and D. delphis. Issue 1 (26th June 2015) - Chivers, Susan J.; Perryman, Wayne L.; Lynn, Morgan S.; Gerrodette, Tim; Archer, Frederick I.; Danil, Kerri; Berman‐Kowalewski, Michelle; Dines, James P.
Abstract: Reproductive parameters were estimated and compared for eastern North Pacific populations of common dolphins using specimen and photogrammetric data. Age and length data for Delphinus capensis and D. delphis specimens recovered as bycatch or strandings were used to estimate the postnatal growth rates needed to estimate age for calves measured in aerial photographs. Bayesian methods propagated uncertainty among models and revealed that the 2009 cohort of calves had birth dates centered on 6 March 2009 for D. capensis and 12 December 2008 for D. delphis . The evidence for discrete calving seasons suggests a mechanism of reproductive isolation has evolved between species. Photogrammetric data and Bayesian methods were also used to estimate the average length at which calves swim independently: 145.1 cm (≈ 11.1 mo) in D. capensis and 140.1 cm (≈ 14.0 mo) in D. delphis, and the proportion of calves (calves/dolphins counted): 0.045 in D. capensis and 0.069 in D. delphis . The latter parameter was converted to an index of calf production (calf/female dolphin) that was >50% lower than pregnancy rates suggesting few births occurred during the study year. Comparisons of regional differences in calf production suggest variability in habitat use patterns within the study area.